Attraction, Environment, Quality of Activities, and Convenience as Predictors of Revisit Intention through Tourist Satisfaction of Visitors to Pakuhaji Destination - Nadhia Noor Kamila; Yadi Ernawadi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of tourist perception which includesattraction, staff service, facilities, information, environment, quality of activities,and cconvenienceagainst revisit intentiontourists to the Pakuhaji tourist destination viatourist satisfactionThis study used a survey method involving tourists who had visited the Pakuhaji tourist destination at least once. The data analysis technique used wasstructural equation modeling(SEM) using SmartPLS software version 3.0. Based on the results of hypothesis testing, it was found that revisit intention is influenced by attraction, environment, quality of activities, and convenience through tourist satisfaction. The novelty in this study lies in the development of a tourist perception model by incorporating quality of activities and convenience which are hypothesized to tourist satisfaction which has not been found in the context of activity-based tourist destinations in Indonesia. The researchers hope that the findings of this study can contribute to the development of tourist behavior studies and become a consideration for Pakuhaji tourist destination managers in designing strategies that can increase tourist revisit intention.